Analisis Aspek Hukum dalam Perjanjian Kredit Bank dengan Jaminan Kebendaan - Dwi Keisya, Fanny; Alya Yumna Zulfa Berti; Tiara Intan Dafitra; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
This research analyzes the legal aspects of bank credit agreements with tangible collateral in Indonesia. Credit agreements with significant collateral play an important role in the banking system by providing security to creditors against the risk of default. This study uses a qualitative approach to assess existing regulations, including mortgage and trust laws, and challenges in their implementation. The findings show that although the existing legal framework is very comprehensive, there are still some challenges in practice, such as low legal certainty, slow implementation process, and high costs. Furthermore, the study examines the legal protection of creditors and debtors and provides recommendations to improve the effectiveness and efficiency of credit agreements with tangible collateral. This research is expected to contribute to the development of better banking laws and better protection of the interests of all parties involved.